A novel silver nanoparticles-based sensing probe for the detection of Japanese Encephalitis virus antigen - Lim, Lih Shan; Chin, Suk Fun; Pang, Suh Cem; Magdline Sia Henry Sum; David Perera (Penerbit Universiti Kebangsaan Malaysia, 2017)
A novel silver nanoparticles (Ag NPs)-based optical sensing probe has been developed for the detection of Japanese Encephalitis virus (JEV). Ag NPs were initially deposited onto amine functionalized glass slides. Subsequently, JEV antibodies were self-assembled onto surfaces of Ag NPs to form optical sensing probes. The detection of JEV antigen was observed via changes in light absorbance by Ag NPs upon occurrence of JEV antigen-antibody bindings. A highly sensitive and rapid optical sensing probe for JEV antigen with a detection limit of 12.8 ng/mL (for S/N ratio = 3) and an analysis assay time of 1 h had been demonstrated.